2015
DOI: 10.1021/nn506074u
|View full text |Cite
|
Sign up to set email alerts
|

Electronic Interaction between Nitrogen Atoms in Doped Graphene

Abstract: Many potential applications of graphene require either the possibility of tuning its electronic structure or the addition of reactive sites on its chemically inert basal plane. Among the various strategies proposed to reach these objectives, nitrogen doping, i.e., the incorporation of nitrogen atoms in the carbon lattice, leads in most cases to a globally n-doped material and to the presence of various types of point defects. In this context, the interactions between chemical dopants in graphene have important… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

13
100
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(114 citation statements)
references
References 56 publications
13
100
1
Order By: Relevance
“…Nevertheless, here, the experiments were repeated multiple times, on several distinct N atoms, systematically yielding a clearly6discernible π* peak. The repeated fast6scanning approach devised by Ramasse et al 24 to obtain high6signal6to6noise spectra from single atoms was also used and yielded again similar results. It should be noted that the experimental possibility of pyridinic defect N configurations was also considered (including theoretical calculations discussed in more detail in Hardcastle et al, in preparation), such as those discussed by Arenal et al, 38 or defects created by damage or atomic jumps.…”
mentioning
confidence: 71%
See 1 more Smart Citation
“…Nevertheless, here, the experiments were repeated multiple times, on several distinct N atoms, systematically yielding a clearly6discernible π* peak. The repeated fast6scanning approach devised by Ramasse et al 24 to obtain high6signal6to6noise spectra from single atoms was also used and yielded again similar results. It should be noted that the experimental possibility of pyridinic defect N configurations was also considered (including theoretical calculations discussed in more detail in Hardcastle et al, in preparation), such as those discussed by Arenal et al, 38 or defects created by damage or atomic jumps.…”
mentioning
confidence: 71%
“…All the predictions on the exact effect of the incorporated dopant atoms in graphene suggest that the resulting band structure depends on the density and periodicity (or not) of the dopant atoms in the graphene lattice, 18,[20][21][22] as well as on the presence of adjacent defects. [23][24][25][26] To add to the complexity of the situation, the synthesis conditions of doped graphene, which most commonly follow the chemical route, yield graphene samples of varying quality, 17 often with several types of dopant atom and defect configurations within the same specimen. [25][26][27] In a bid to produce uniformly6doped single6 layer graphene specimens, the successful implementation of low6energy ion implantation with either N or B was recently demonstrated, [28][29][30] achieving retention levels of the order of ~1% in good agreement with theoretical predictions.…”
mentioning
confidence: 99%
“…To partially overcome these problems the theoretical calculations in the frame of DFT were performed. The influence of the graphitic-N and pyridinic-N configurations on the STM images has been already determined by the DFT calculations [10,12,16,22,48]. Besides these two most common configurations, attempts to calculate STM images of more complex structures were performed [13].…”
Section: Identification Of Nitrogen-carbon Bonds Typementioning
confidence: 99%
“…Besides these two most common configurations, attempts to calculate STM images of more complex structures were performed [13]. Recently it has been shown that the changes in the graphene local electronic properties observed in the STM images can be related to the interaction between nitrogen atoms located at the same or different sublattices [48]. These results can be very useful during identification of nitrogen bond type basing on the STM measurements.…”
Section: Identification Of Nitrogen-carbon Bonds Typementioning
confidence: 99%
“…6,12,13 Most experimental work so far has involved boron and nitrogen substitutions at single C sites. [14][15][16][17][18] These are either incorporated into the lattice during chemical vapor deposition growth 14,17 or afterward by ion irradiation and annealing 15 and provide p-and n-type doping, respectively. A common challenge in functionalizing graphene through defect engineering is in the defects' relatively high formation energy and their tendency to cluster, 7,19 which further motivates study in defect creation and control.…”
Section: Introductionmentioning
confidence: 99%